El Aprendizaje Basado en Problemas para la enseñanza aprendizaje de la asignatura de Física de Segundo de Bachillerato General Unificado - Correa Sanchez, Paola Soledad (2023)
The objective of this research is to analyze the Problem-Based Learning method in the importance of the Physics teaching-learning process, it has a qualitative research approach with documentary design, supported by the bibliographic review research method, using the checking technique by means of content and bibliographic cards instruments. For the processing of the information, time lines were used for each of the variables, in this way it was possible to arrive at the results and discuss them, concluding that Problem-Based Learning is important for the teaching-learning process because it generates in the student skills necessary for current education such as: autonomy, knowledge construction, critical thinking and the possibility of contextualizing reality with the theoretical contents. Key words: Problem-Based Learning, teaching methodoly, teaching-learning, physics.